2023
DOI: 10.21203/rs.3.rs-2505658/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of Meeting 24-hour Movement Behavior Guidelines with Cognitive Difficulty and Social Relationships in Children and Adolescents with Attention Deficit/Hyperactive Disorder

Abstract: Background: Evidence-based 24-hour movement behavior (24-HMB) guidelines have been developed to integrate recommendations for the time spent in the behaviors of physical activity, sedentary behavior, and sleep. For children and adolescents, these 24-HMB guidelines recommend a maximum of two hours of recreational screen time (as part of sedentary behavior), a minimum of 60 minutes per day of moderate to vigorous physical activity (MVPA), and age-appropriate sleep duration (9-11 hours for 5 to 13-year-olds; 8-10… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…Our study found that, compared with children with TD, children with ADHD engaged less time in MVPA daily (101.00 min·d −1 vs 84.19 min·d −1 ) and had a lower proportion to meet the MVPA guidelines (93% vs 78%). It was noted that previous findings on accelerometer-measured MVPA and subjective reports on 60 min of MVPA guideline attainment on children with ADHD are mixed (38.47, 51.75, and 27.57 min·d −1 ) (10,19,31,32), and MVPA disparities in children with ADHD warrant further investigation. Moreover, the 2020 WHO Guidelines on Physical Activity and Sedentary Behaviours recommended that children and adolescents with living disabilities engage in at least 60 min of MVPA daily, including children with ADHD (33).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study found that, compared with children with TD, children with ADHD engaged less time in MVPA daily (101.00 min·d −1 vs 84.19 min·d −1 ) and had a lower proportion to meet the MVPA guidelines (93% vs 78%). It was noted that previous findings on accelerometer-measured MVPA and subjective reports on 60 min of MVPA guideline attainment on children with ADHD are mixed (38.47, 51.75, and 27.57 min·d −1 ) (10,19,31,32), and MVPA disparities in children with ADHD warrant further investigation. Moreover, the 2020 WHO Guidelines on Physical Activity and Sedentary Behaviours recommended that children and adolescents with living disabilities engage in at least 60 min of MVPA daily, including children with ADHD (33).…”
Section: Discussionmentioning
confidence: 94%
“…The multitude of biopsychosocial risk factors that caused sleep problems in children with ADHD has been proposed, including biological (e.g., sleep-wake cycle and circadian rhythm), psychological (e.g., co-occurring mental health problems), and contextual factors (e.g., PA levels) (11). One recent cross-sectional study in 3470 children with ADHD using the National Survey for Children's Health (NSCH 2020) reported that only 4.9% of participants met 60 min of MVPA guidelines and that 26.9% of participants had sufficient sleep (19). Although the emerging associations between higher daytime MVPA and minor sleep latency (20), short sleep duration and severe ADHD symptoms (21), and lower motor proficiency and severer sleep problems (11) in children with ADHD have been reported, little research has examined the relationships among MVPA, motor proficiency, and sleep quality in children with ADHD.…”
mentioning
confidence: 99%
“…Particularly, a better understanding of meeting 24-HMB guidelines among youth with MBD conditions represents a critical step before strategies for this disadvantaged population can be developed and implemented. Meeting 24-HMB guidelines among youth have been documented in parts of Korea, China, Australia and the U.S. [14,15,23,24], but U.S.-based studies have thus far been limited to either only single conditions of MBD[18, 24,25] or the majority of data among youth have relied on cross-sectional designs [15,19,26]. Recent trends in meeting 24-HMB guidelines among youth with MBD conditions have not been well described.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of obesity is very high (Faraone et al, 2021), with some studies reporting an increased prevalence of 40% compared to children without ADHD (Cortese et al, 2016). There is therefore a need to support increases in MVPA for children with ADHD (Taylor et al, 2023).…”
Section: Introductionmentioning
confidence: 99%